Consequences and causes of corruption: What do we know from a cross-section of countries? - Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2005)
Data on the perceived levels of corruption from a cross-section of countries has been introduced fruitfully into recent empirical research. This chapter reviews studies on the consequences and causes of corruption. It includes research on the impact of corruption on investment, GDP, institutional quality, government expenditure, poverty, international flows of capital, goods and aid. Causes of corruption focus on absence of competition, policy distortions, political systems, public salaries as well as an examination of colonialism, gender and other cultural dimensions.
Keywords: H3; K42; O57; 330